Perhitungan Kebutuhan Bahan Baku Tas untuk Meningkatkan Efisiensi Produksi dan Mengurangi Biaya Kerugian: - Muhammad Hafidz Syarifudin; Siti Mundari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The bag convection industry in Indonesia is experiencing rapid growth along with increasing market demand. CV. Aurellia Jaya as one of the bag manufacturers faces a major problem in the form of a lack of raw material inventory which results in production delays and increased financial costs that must be borne. This study aims to calculate raw material requirements and the cost of losses due to late delivery to customers. The method used is the Silver–Meal Heuristic to determine the optimal timing and quantity of raw material orders, as well as cost analysis to measure losses in labor, machinery, and estimated delivery. The results show that the ordering cost is Rp1,704,000, the holding cost is Rp998,884, and the total inventory cost is Rp2,702,884, with a lot size of 6,488 rolls in 4 ordering cycles. The safety stock that must be provided is 176 rolls and the reorder point is at 786 rolls, and the total loss due to delays is Rp46,812,500 per 12 periods. The application of the Silver–Meal Heuristic method and Cost Analysis has been proven to make raw material inventory more efficient without raw material shortages and large losses for the company.